Achieving Value in Spine Surgery: 10 Major Cost Contributors. Issue 1 (April 2021) - Philipp, Lucas R.; Leibold, Adam; Mahtabfar, Aria; Montenegro, Thiago S.; Gonzalez, Glenn A.; Harrop, James S.
Study Design: Narrative Review. Objectives: The increasing cost of healthcare overall and for spine surgery, coupled with the growing burden of spine-related disease and rising demand have necessitated a shift in practice standards with a new emphasis on value-based care. Despite multiple attempts to reconcile the discrepancy between national recommendations for appropriate use and the patterns of use employed in clinical practice, resources continue to be overused—often in the absence of any demonstrable clinical benefit. The following discussion illustrates 10 areas for further research and quality improvement. Methods: We present a narrative review of the literature regarding 10 features in spine surgery which are characterized by substantial disproportionate costs and minimal—if any—clear benefit. Discussion items were generated from a service-wide poll; topics mentioned with great frequency or emphasis were considered. Items are not listed in hierarchical order, nor is the list comprehensive. Results: We describe the cost and clinical data for the following 10 items: Over-referral, Over-imaging & Overdiagnosis; Advanced Imaging for Low Back Pain; Advanced imaging for C-Spine Clearance; Advanced Imaging for Other Spinal Trauma; Neuromonitoring for Cervical Spine; Neuromonitoring for Lumbar Spine/Single-Level Surgery; Bracing & Spinal Orthotics; Biologics; Robotic Assistance; Unnecessary perioperative testing. Conclusions: In the pursuit of value in spine surgery we must define what quality is, and what costs we are willing to pay for each theoretical unit of quality. We illustrate 10 areas for future research and quality improvement initiatives, which are at present overpriced and underbeneficial.